The political theory of Aristophanes : explorations in poetic wisdom - Mhire, Jeremy J., 1977-; Frost, Bryan-Paul, 1961- (Albany, NY : SUNY Press, 2014)
His original and wide-ranging collection of essays offers, for the first time, a comprehensive examination of the political dimensions of that madcap comic poet Aristophanes. Rejecting the claim that Aristophanes is little more than a mere comedian, the contributors to this fascinating volume demonstrate that Aristophanes deserves to be placed in the ranks of the greatest Greek political thinkers. As these essays reveal, all of Aristophanes' plays treat issues of fundamental political importance, from war and peace, poverty and wealth, the relation between the sexes, demagoguery and democracy to the role of philosophy and poetry in political society. Accessible to students as well as scholars, "The Political Theory of Aristophanes" can be utilized easily in the classroom, but at the same time serve as a valuable source for those conducting more advanced research. Whether the field is political philosophy, classical studies, history, or literary criticism, this work will make it necessary to reconceptualize how we understand this great Athenian poet and force us to recognize the political ramifications and underpinnings of his uproarious comedies
""Chapter 12: The Comedy of the Just City: Aristophanesâ€? Assemblywomen and Platoâ€?s Republic""""I. Introduction""; ""II. Praxagoraâ€?s Design""; ""III. The Platonic Adaption of Praxagoraâ€?s Design""; ""IV. Aristophanes and Plato""; ""Notes""; ""Chapter 13: Peisetairos of Aristophanesâ€? Birds and the Erotic Tyrant of Republic IX""; ""I. The Erotic Tyrant of Republic IX""; ""II. Plato on Two Kinds of Eros""; ""III. Tyrannical Eros in the Symposium""; ""IV. Eros Tyrannos and Aristophanesâ€? Birds""; ""V. Interpreting the Birds""; ""VI. The Ancient Quarrel between Plato and Aristophanes?""
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Aristophanes -- Criticism and interpretation; Aristophanes; Aristophanes; 18.43 ancient Greek literature; DRAMA -- Ancient, Classical & Medieval; PHILOSOPHY / Political; Criticism, interpretation, etc